Konsep Tobat menurut Imam Al-Qusyairi - Erwin Erwin (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the concept of repentance according to Imam Al-Qusyairi and how it is applied in everyday life. This study is expected to provide a scientific contribution to add to the treasures of knowledge in the field of Sufism. This reseatch is expected to be a source of reference for future researchers who wish to conduct similar studies. In this study the author uses a qualitative method. This method is also known as the interpretive method and places the researcher as the core instrument. The technique used in data collection is a literature study by exploring various relevant sources. According to Qusyairi, repentance is a sincere request for forgiveness. The orientation of this concept refers to statements, promises, and responbilities. Repentance is not just words, repentance also means a promise not to make the same mistake. The promise must be held firmly with full responsibility. Repentance in his view takes place continuously. No words of despair and give up in the process of repentance. Allah will always open the door of repentance for his servants who always ask Allah for forgiveness. The concept of repentance Al-Qusyairi is very relevant to be applied in this era. Modernity has created an affliction that stimulates various crises. Modernity also brings freedom, so that humans lose control in their actions, errors that are prone to acur can be overcomeby understanding the concept of repentance and applying it in life.